2004
DOI: 10.1593/neo.04241
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Erk Pathway Is Required for TGF-β1-Induced EMT In Vitro

Abstract: Transforming growth factor-beta1 (TGF-beta1) can be tumor-suppressive through the activation of the Smad-mediated signaling pathway. TGF-beta1 can also enhance tumor progression by stimulating epithelial-to-mesenchymal transition (EMT) through additional pathways. EMT is characterized by the acquisition of a fibroblast-like cell morphology, dissolution of tight junctions, disruption of adherence junctions, and formation of actin stress fibers. There is evidence linking the activation of mitogen-activated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
364
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(413 citation statements)
references
References 33 publications
35
364
4
Order By: Relevance
“…It is well known that the down-regulation of E-Cad expression is the hallmark of epithelial plasticity (9,41). Our data demonstrated that AuNP treatment resulted in a substantial increase in E-Cad expression with simultaneous decrease in Vimentin, Snail, and N-Cad expression in ovarian cancer cells, further supporting anti-EMT function of unmodified AuNPs (Fig.…”
Section: Aunp Treatment Inhibits Tumor Growth and Metastasis In Vivo Bysupporting
confidence: 79%
See 1 more Smart Citation
“…It is well known that the down-regulation of E-Cad expression is the hallmark of epithelial plasticity (9,41). Our data demonstrated that AuNP treatment resulted in a substantial increase in E-Cad expression with simultaneous decrease in Vimentin, Snail, and N-Cad expression in ovarian cancer cells, further supporting anti-EMT function of unmodified AuNPs (Fig.…”
Section: Aunp Treatment Inhibits Tumor Growth and Metastasis In Vivo Bysupporting
confidence: 79%
“…Together the results obtained from qRT-PCR and the cytokine array indicate that the AuNP treatment in the ovarian cancer cell lines does modulate the expression of the growth both at the transcriptional and translational level. Since the proteins discussed above are collectively known to induce EMT (19,25,41), these results suggest a possible anti-EMT function of AuNPs.…”
Section: Aunp Treatment Inhibits Tumor Growth and Metastasis In Vivo Bymentioning
confidence: 82%
“…Under these conditions, EMT is defined as the occurrence of a variable proportion of tumor cells that upregulate mesenchymal markers such as vimentin and snail, and that downregulate epithelial markers such as E-cadherin (17,18). The expression of these EMT markers is induced by a number of growth factor/receptor systems such as the hepatocyte growth factor (HGF)/c-met system (19)(20)(21) and the transforming growth factor (TGF)-ß/TGF-ß receptor system (22,23), both of which are associated with a more aggressive phenotype of cancer cells. However, little information is available regarding the type of EMT induced by chemokine system(s), including the SDF-1/CXCR4 system, despite abundant evidence of the diverse malignant behaviors of such systems in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of cross-talk between Ras and TGF-h/Smad signaling have been described during the last decade (31)(32)(33)(34)(35). Yue et al (31) reported that TGF-h activated the Ras/MAPK pathway required for the autocrine TGF-h production and Smad1 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Ras was also suggested as a mediator of pleiotropic TGF-h1 signaling in developing neurons (32). The activation of Ras/MAPK or the presence of oncogenic Ras was shown to enhance TGF-hinduced epithelial-mesenchymal transition (33,34). More importantly, it has been shown that 1a,25(OH) 2 D 3 regulates the MAPK pathway by activating Ras/RAF-1 signaling in muscle cells and in myeloid leukemic cells (17,18).…”
Section: Discussionmentioning
confidence: 99%